UJI KISARAN INANG POTYVIRUS PENYEBAB MOSAIK NILAM (Pogostemon cablin (Blanco) Benth) ASAL SULAWESI TENGGARA - HASAN, ASMAR; TAUFIK, MUHAMMAD; -, GUSNAWATY HS; -, SARAWA (Jurnal Agroteknos, 2014)
The objective of the research was to determine the host alternate of Potyvirus in Southeast Sulawesi using a host range technique. Observed variables were incubation period, disease incidence, and variation symptom. The research results showed that virus isolates could be mechanically transmitted to melon plant (Cucumismelo) but showing no external symptoms while on tomato (Solanum lycopersicum), long-beans (Vigna sinensis), tobacco (Nicotiana tabacum and Nicotiana benthamiana), swamp-land (Ipomoea reptana), red-amaranth (Alternantheraamoena), chili (Capsicum annum), and egg plant (Solanum melongena) so far the existence of the Potyvirus could not be detected after mechanically inoculated.